2019
DOI: 10.1016/j.jimonfin.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Macroprudential policy, central banks and financial stability: Evidence from China

Abstract: We study the Chinese experience and provide evidence that central banks can play an active role in safeguarding financial stability. The narrative approach is used to disentangle macropudential policy actions from monetary actions. We show that reserve requirements, window guidance, supervisory pressure and housing-market policies can be used for macroprudential purposes. Our VAR estimates suggest that well-targeted macroprudential policy has immediate and persistent impact on credit, but no statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 70 publications
3
41
0
Order By: Relevance
“…19 In addition to the SLF, the central bank has other liquidity injection tools with longer tenors of 3-month, 6-month and 1year, namely the Medium-term Lending Facility (MLF) that was introduced in September 2014. However, a preliminary assessment done in Sun (2018) indicates that the immediate effects of changes in these two central bank lending rates on market interest rates are limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition to the SLF, the central bank has other liquidity injection tools with longer tenors of 3-month, 6-month and 1year, namely the Medium-term Lending Facility (MLF) that was introduced in September 2014. However, a preliminary assessment done in Sun (2018) indicates that the immediate effects of changes in these two central bank lending rates on market interest rates are limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Rather, clear communication and transparency are crucial for this system to function well in transmitting policy changes to financial markets (see, e.g., Bernanke and Kuttner 2005;Kuttner 2001). With a target interest rate system, the PBC needs to clearly announce which money market rate it is targeting and its explicit target rate in order to effectively guide markets (Sun 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…So, capital and liquidity must fulfill the requirements of organizations" regulations, such as under Basel III. Thus these regulations help in increasing the bank"s resilience, which is, in turn, absorb shocks, such as oil prices decline (Klingelhöfer & Sun, 2019). It is also reported that low liquidity has a significant and negative effect on bank compliance to rule and regulations that have proposed by Basel III.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Central bank macroprudential policies always have an impact on financial stability. In particular, this was explored in Klingelhöfer and Sun (2019) in the case of China, which identified an immediate and ongoing impact on lending, maintaining financial stability without slowing economic growth. The policy is a complement to monetary policy to offset financial risks.…”
Section: Literature Reviewmentioning
confidence: 99%